2011
DOI: 10.1021/jo2007785
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin-Based Polycationic Amphiphilic “Click” Clusters: Effect of Structural Modifications in Their DNA Complexing and Delivery Properties

Abstract: Monodisperse facial amphiphiles consisting of a β-cyclodextrin (βCD) platform exposing a multivalent display of cationic groups at the primary rim and bearing hydrophobic chains at the secondary oxygens have been prepared by implementing two very robust "click" methodologies, namely cuprous cation-catalyzed azide-alkyne cycloaddition (CuAAC) and thiourea-forming reaction. Most interestingly, the use of solid-supported Cu(I) catalysts was found to be very well suited for multiple CuAAC while facilitating purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 91 publications
(48 reference statements)
1
54
0
Order By: Relevance
“…The increasing awareness of the potential of polycationic CD derivatives in the design of nonviral gene delivery systems has led several groups to explore the suitability of polycationic CD conjugates to impart, simultaneously, stability and targeting capabilities of the corresponding complexes with plasmid DNA (pDNA), for which the term CDplexes has been coined. [148][149][150][151][152][153][154][155][156][157] Uekama, Arima and co-workers conceived a series of multifunctional CD conjugates consisting of a poly(amidoamine) (PAMAM) starburst dendrimer 102 onto which one-to-two aCD units (103) were randomly attached through a single primary (C-6) position by reaction with the corresponding 6 Itosyl derivative 103. Some of the remaining primary amino groups of the dendrimer were subsequently engaged in thiourea forming reactions with isothiocyanate-armed aMan (104) and aGal derivatives to afford the corresponding polycationic aCD-PAMAM glycoconjugates.…”
mentioning
confidence: 99%
“…The increasing awareness of the potential of polycationic CD derivatives in the design of nonviral gene delivery systems has led several groups to explore the suitability of polycationic CD conjugates to impart, simultaneously, stability and targeting capabilities of the corresponding complexes with plasmid DNA (pDNA), for which the term CDplexes has been coined. [148][149][150][151][152][153][154][155][156][157] Uekama, Arima and co-workers conceived a series of multifunctional CD conjugates consisting of a poly(amidoamine) (PAMAM) starburst dendrimer 102 onto which one-to-two aCD units (103) were randomly attached through a single primary (C-6) position by reaction with the corresponding 6 Itosyl derivative 103. Some of the remaining primary amino groups of the dendrimer were subsequently engaged in thiourea forming reactions with isothiocyanate-armed aMan (104) and aGal derivatives to afford the corresponding polycationic aCD-PAMAM glycoconjugates.…”
mentioning
confidence: 99%
“…In general, cationic polymers, poly-L-lysines (PLL) and poly-L-arginines (PLA) [126,127]; (c) carbohydrate-based polymers in which the charge is mainly supplied by cationic cyclodextins, glycoamines and so on [128][129][130]; and (d) dendrimers-based polymers as polyamidoaminme (PAMAM) and others [131][132][133]. In addition, electrostatic interaction has been also analyzed in complexes where polycations, based on amphiphilic polycationic cyclodextrins [100,134,135] and calixarenes [136], were used as gene vectors of plasmid DNA or siRNA.…”
Section: Electrostatic Interactionmentioning
confidence: 99%
“…(ii) multivalent cationic lipids [67,78,139,178,181], derivated oligoamines [182] and tripeptide multivalent lipids [122]; (iii) cationic polymers derivatives from PEI [124,127,183,184], PAMAM [132,140], PDMAEMA [123,133,185], PAA [103,131,186,187], chitosan [188], polyphosphoramidates [189], polyhydroxyalkanoate [92], polyamines [107], polyaminoacids [127,190] or diblock copolymers [191]; (iv) polycations from calixarene [40,136,165,192] or cyclodextrin [134,135,142,164,193] derivatives; (v) lipopolymers from lysine derivatives [170]; (vi) pendant polymercationic cyclodextrins [129,130,163]; and (vii) cationic polymer-cyclodextrin polyrotaxanes [89]. The picture that results from these transfection studies is that many of the polyplexes show efficacies comparable to that reported by the Lipo2000 positive control and also by most of the commercial or synthezised univalent CLs, but its efficacy as transfecting agents of DNA is still below than that reported by most of t...…”
Section: Biochemistry Characterizationmentioning
confidence: 99%
“…R f : 0.46 (methanoldichloromethane 15:85). (11). To a solution of thymidine 10 (5 g, 20.6 mmol, 1.0 equiv) in pyridine (125 mL) was added DMAP (0.126 g, 1.03 mmol, 0.05 equiv.)…”
Section: (S)-4-(1-(((2r3s5r)-3-hydroxy-5-(5-methyl-24-dioxo-3-(promentioning
confidence: 99%
“…The chemical combination of biological molecules such as nucleic acids [1][2][3], aminoacids [4], peptides [5][6][7][8] or sugar [9][10][11] with lipids, remains an amazing approach to create new hybrid amphiphilic structures. Owning to their biocompatibility properties and biological functions, hybrid amphiphiles hold considerable potential for biomedical and biotechnological applications.…”
Section: Introductionmentioning
confidence: 99%